2012
DOI: 10.1016/j.optlaseng.2012.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Direct Laser Fabrication process with coaxial powder projection of 316L steel. Geometrical characteristics and microstructure characterization of wall structures

Abstract: Direct Laser Fabrication is a promising manufacturing technology. A moving laser beam heats a coaxially delivered powder in a gas jet through nozzle in order to fabricate an end-use part directly. The clad geometry is an important process characteristic. In this work, different velocities and different laser shift-distances between two successive layers are used to build walls. For each condition, 1, 3, 5 and 10 layers walls are analyzed, showing the domain of a success and optimal construction. A relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(22 citation statements)
references
References 18 publications
0
21
0
1
Order By: Relevance
“…These fine sub-grain microstructures and fine distribution of particular elements are confirmed beneficial to the alloy’s hardness, strength, ductility (known as defect-tolerant) [14,25], and thermal conductivity performance under some circumstances [26]. This kind dynamical formation of three-dimensional arrays of cells and bands structures are also very common in high energy beam material processing and rapid solidification, e.g., welding [27,28,29,30], surface melting [31,32,33], space directional solidification [34,35], laser cladding or laser engineered shaping (LENSTM) [36,37,38,39,40]. These technologies have common features with SLM of constrained crystal growth, so the similar microstructures can be fabricated.…”
Section: Introductionmentioning
confidence: 99%
“…These fine sub-grain microstructures and fine distribution of particular elements are confirmed beneficial to the alloy’s hardness, strength, ductility (known as defect-tolerant) [14,25], and thermal conductivity performance under some circumstances [26]. This kind dynamical formation of three-dimensional arrays of cells and bands structures are also very common in high energy beam material processing and rapid solidification, e.g., welding [27,28,29,30], surface melting [31,32,33], space directional solidification [34,35], laser cladding or laser engineered shaping (LENSTM) [36,37,38,39,40]. These technologies have common features with SLM of constrained crystal growth, so the similar microstructures can be fabricated.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the range of processing parameters is rather narrow for the production of samples with dimensional stability and microstructure integrity. El Cheikh et al [ 2 ] investigated the process of the direct laser fabrication (DLF) of products made of 316 L steel, studying, for example, the effect on the laser spot speed and the different laser shift-distances between two successive layers. Interactions between the process parameters were found.…”
Section: Introductionmentioning
confidence: 99%
“…The vertically deposited single clad is normally considered to be a fundamental pillar for obtaining the map of process parameters, as shown in the work of de Oliveira et al [12]. The objective is to select one or more conditions for further studies of the overlap clad, as done in previous works using Eutroloy 16606A as a filler material [13] and by laser cladding of multilayer walls reported by El Cheikh et al [14] and Arregui et al [15]. However, there is no viable experimental argument for rejecting single clad parameters that are based on overlap percentages or multilayer structures.…”
Section: Introductionmentioning
confidence: 99%